Perubahan Regulasi Pengelolaan Keuangan BUMN Menurut Undang-Undang No 1 Tahun 2025 tentang Badan Usaha Milik Negara: Tinjauan Filosofi Hukum - Rasji; Yuniati; Zayyan Syafiqah Aggistri (CV Rewang Rencang, 2024)
State-Owned Enterprises (SOEs) in Indonesia play an important role in the economy, but face challenges in transparency and accountability after Law No. 1 of 2025. This study analyzes changes in SOE financial management from a philosophical legal perspective. The results show that the elimination of the phrase